PENGARUH PERHATIAN GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SDN TEBET TIMUR 17 - Azka Nur Izzati; Maria Ulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of teacher's attention on the intrinsic learning motivation of sixth-grade students at SDN Tebet Timur 17. The study was motivated by the low participation and enthusiasm shown by some students during the learning process, which was suspected to be related to the degree of attention given by their teachers. A quantitative approach with a correlational method was used. The population consisted of 52 sixth-grade students from two classes, all of whom served as respondents through a saturated sampling technique. Data were collected using a Likert-scale questionnaire covering teacher's attention (X) and students' learning motivation (Y), then analyzed using the Pearson Product Moment correlation formula assisted by SPSS 22. The results show a Pearson correlation coefficient (r-count) of 0.636 between teacher's attention and learning motivation, which is greater than the r-table value of 0.2732 at a 5% significance level, with a significance value of 0.000 (< 0.01). This indicates a positive and significant relationship in the moderate category. The coefficient of determination (R²) of 0.404 shows that teacher's attention accounts for 40.4% of the variance in students' learning motivation, while the remaining 59.6% is explained by other factors outside this study. It is concluded that teacher's attention has a positive and significant effect on students' intrinsic learning motivation, so that sustained and structured attention from teachers, such as guidance, positive reinforcement, and responsive feedback, is expected to further strengthen students' learning motivation